Correlation Between Exercise Frequency and Menstrual Cycle Characteristics in Perimenopausal Women Aged 45–50 Years - Ni Luh Kadek Alit Arsani; Luh Ari Arini; Luh Yenny Armayanti; Komang Hendra Prasetiawan; Made Satya Nugraha Gautama (Althea Medical Journal, 2026)
Background: During perimenopause, declining estrogen levels often lead to altered menstrual patterns and other age-related health concerns. Consequently, the role of physical activity warrants closer examination. This study investigated the correlation between exercise frequency and menstrual cycle characteristics in premenopausal womenMethods: A cross-sectional observational study was conducted in Singaraja City, Indonesia, from July to October 2024. A total of 150 premenopausal women aged 45–50 years were recruited through random sampling. Exercise frequency was measured using the World Health Organization’s Global Physical Activity Questionnaire (GPAQ) and categorized as never, low (1–2 times/week), moderate (3–4 times/week), and high (>5 times/week). Menstrual cycle characteristics were assessed according to the International Federation of Gynecology and Obstetrics (FIGO) criteria, including cycle frequency, regularity, duration, and sanitary product use. Correlations between exercise frequency and menstrual parameters were analyzed using Spearman’s Rho test.Results: Almost half of the women (45.3%) exercised 1–2 times/week. Interestingly, 22.0% never exercised. Moderate negative correlations were observed between exercise frequency and menstrual cycle period (r=-0.35, p<0.001) as well as regularity (r=-0.42, p<0.001). However, no significant correlation was found between exercise frequency and menstrual duration, and only a weak negative correlation with sanitary product use (r=-0.17, p=0.038).Conclusions: Physical activity appears to modulate menstrual cycle patterns during perimenopause. Consequently, regular exercise may facilitate hormonal homeostasis and support reproductive health throughout the menopausal transition, ultimately enhancing overall quality of life